The Lifeworlds of Law: On Revitalizing Indigenous Legal Orders Today - Mills, Aaron (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2016)
What ultimately counts as law and as the legitimate processes of its generation, adjustment, and destruction are both empowered and constrained by the constitutional order from which they derive life. A constitutional framework, in turn, reflects unique understandings about what there is and how one can know: a lifeworld. Reflecting on his own experience, the author emphasizes how legal education harms when it fails to acknowledge and to begin to articulate the lifeworld beneath any system of law it aims to impart.There are serious questions to be taken up in considering whether we may move law between constitutional contexts without subjugating the law of one community to the lifeworld of another. The author asserts this is particularly important with respect to Canadian law schools’ recent interest in teaching Indigenous peoples’ own systems of law. He argues that Canadian (liberal) and Indigenous (what he calls “rooted”) constitutionalisms are not only different, but different in kind. As such, efforts to articulate Indigenous law within the forms of liberal constitutionalism ignore or trivialize the ongoing significance of Indigenous lifeworlds to governance of Indigenous lives today. Many Indigenous legal scholars are adverting to this tension, moving on from simply making space for Indigenous law in the academy to asking whether and how this may be done. The author briefly canvasses Indigenous theorists (students, professors, lawyers, and elders) whose works present Indigenous systems of law within their own lifeworlds.Tracking the lifeworld-law relationship, he proposes three reforms to legal education in Canada: (1) teach that all law is storied; (2) teach that Canadian constitutional law is a species of liberal constitutionalism; (3) require students to enrol in a prerequisite on an Indigenous people’s constitutional order before enrolling in a course on their law. By way of example, he concludes with the syllabus for an intensive course he designed and taught on Anishinaabe constitutionalism.